Gender, Estrogen, and Obliterative Lesions in the Lung - Hamza Assaggaf; Quentin Felty (International Journal of Endocrinology)
Gender has been shown to impact the prevalence of several lung diseases such as cancer, asthma, chronic obstructive pulmonary disease, and pulmonary arterial hypertension (PAH). Controversy over the protective effects of estrogen on the cardiopulmonary system should be of no surprise as clinical trials of hormone replacement therapy have failed to show benefits observed in experimental models. Potential confounders to explain these inconsistent estrogenic effects include the dose, cellular context, and systemic versus local tissue levels of estrogen. Idiopathic PAH is disproportionately found to be up to 4 times more common in females than in males; however, estrogen levels cannot explain why males develop PAH sooner and have poorer survival. Since the sex steroid hormone 17β-estradiol is a mitogen, obliterative processes in the lung such as cell proliferation and migration may impact the growth of pulmonary tissue or vascular cells. We have reviewed evidence for biological differences of sex-specific lung obliterative lesions and highlighted cell context-specific effects of estrogen in the formation of vessel lumen-obliterating lesions. Based on this information, we provide a biological-based mechanism to explain the sex difference in PAH severity as well as propose a mechanism for the formation of obliterative vascular lesions by estrogens.